THE SUSCEPTIBILITY OF LABORATORY ANIMALS TO TRYPANOSOMA EVANSI INFECTIONS - HASAN BASRI MUNAF (Research Center for Biology-Indonesian Institute of Sciences, 1981)
Trypanosoma evansi, one of about 200 trypanosomes species encountered in mammals in the world, is the causative agent of an economically important disease among domestic animals called surra. Many studies on T. evansi has been made using various experimental animals such as chicks and fowls for kifectivity (Alwar 1962, Manuel & Cajita 1967), mice for influences of temperature (Marthur 1976) and rats for immunological studies (Assoku 1975). Even larger animals such as goats, pigs, horses, cattle and buffaloes have been used by several workers in studying T. evansi infections (Chand & Singh 1971, Gill 1971, Srivastava & Ahluwalia 1972).The present paper deals with the susceptibilities of small laboratory animals to T. evansi infections in order to determine which animals are suitable for maintaining T. Svansi in the laboratory. All works in this study were done at the Filariasis Research Division of the Institute for Medical Research (IMR), Kuala Lumpur.